Isoprene in the Exhaled Breath is a Novel Biomarker for Advanced Fibrosis in Patients with Chronic Liver Disease: A Pilot Study. Issue 9 (September 2015) - Alkhouri, Naim; Singh, Tavankit; Alsabbagh, Eyad; Guirguis, John; Chami, Tarek; Hanouneh, Ibrahim; Grove, David; Lopez, Rocio; Dweik, Raed
Abstract : OBJECTIVES: : Analysis of volatile organic compounds (VOCs) in the exhaled breath can identify markers for alcoholic and nonalcoholic fatty liver disease. The aim of this pilot study was to investigate the utility of breath VOCs measured by mass spectrometry to diagnose advanced fibrosis in patients with chronic liver disease (CLD). METHODS: : Patients undergoing liver biopsy were recruited. Fibrosis was determined by an experienced pathologist (F0–4) and advanced fibrosis was defined as F3–4. Exhaled breath and plasma samples were collected on the same day of the biopsy. Selective ion flow tube mass spectrometry (SIFT‐MS) was used to analyze breath samples. Bonferroni correction was applied to decrease the false discovery rate. RESULTS: : In all, 61 patients were included with a mean age of 50.7±9.9 years and 57% were male. Twenty patients (33%) had advanced fibrosis (F3–4), 44% had chronic hepatitis C, 30% had nonalcoholic fatty liver disease, and 26% had other CLD. SIFT‐MS analysis of exhaled breath revealed that patients with advanced fibrosis had significantly lower values of six compounds compared with those without advanced fibrosis, P value <0.002 for all. Isoprene was found to have the highest accuracy for the prediction of advanced fibrosis with an area under the receiver operating characteristics curve of 0.855 (95% confidence interval: 0.762, 0.948). The median breath isoprene level in patients with F3–4 was 13.5[8.7, 24.7] p.p.b. compared with 40.4[26.2, 54.1] for those with F0–2, P value <0.001. Isoprene is an endogenous VOC that is a byproduct of cholesterol biosynthesis. CONCLUSIONS: : Isoprene is a potential biomarker for advanced fibrosis that deserves further validation.